Incorporation of UDPGlucose into Cell Wall Glucans and Lipids by Intact Cotton Fibers - Dugger, W. M. (1986)
The [(14)C] moiety from [(3)H]UDP[(14)C]glucose was incorporated by intact cotton fibers into hot water soluble, acetic-nitric reagent soluble and insoluble components, and chloroform-methanol soluble lipids; the [(3)H] UDP moiety was not incorporated. The (3)H-label can be exchanged rapidly with unlabeled substrate in a chase experiment. The cell wall apparent free space of cotton fibers was in the order of 30 picomoles per milligram of dry fibers; 25 picomoles per milligram easily exchanged and about 5 picomoles per milligram more tightly adsorbed. At 50 micromolar UDPglucose, 70% of the [(14)C]glucose was found in the lipid fraction after both a short labeling period and chase. The percent of [(14)C]glucose incorporated into total glucan increased slightly with chase, but the fraction of total glucans incorporated into insoluble acetic-nitric reagent (cellulose) did increase within a 30-minute chase period. The data supports the concept that glucan synthesis, including cellulose, as well as the synthesis of steryl glucosides, acetylated steryl glucosides, and glucosyl-phosphoryl-polyprenol from externally supplied UDPglucose occurs at the plasma membrane-cell wall interface. The synthase enzymes for such synthesis must be part of this interfacial membrane system.